Precautionary Debt Capacity - Deniz Aydin; Olivia S. Kim (ZBW - Leibniz Information Centre for Economics, 2024)
Firms with ample financial slack are unconstrained... or are they? In a field experiment that randomly expands debt capacity on business credit lines, treated small-and-medium enterprises (SMEs) draw down 35 cents on the dollar of expanded debt capacity in the short-run and 55 cents in the long-run despite having debt levels far below their borrowing limit before the intervention. SMEs direct new borrowing to financing investment gradually over time and do not exhibit a measurable impact on delinquencies. Heterogeneity analysis by the risk of being at the credit line limit supports the SME motive to preserve financial flexibility.
Keywords: 330; field experiment; RCT; finance; investment; debt structure